MODELING AND SIMULATION OF TEMPERATURE FIELD FOR FREEZE FABRICATION PROCESS - YANG LeiPeng; LI ShuJuan; JIAO PanDe; WU XueLiang (Jixie qiangdu)
Freeze fabrication process is a new modern green additive manufacturing technology. During the depositing process,the freezing time needed would change with the increase of the deposition layer. The paper established the temperature field model of deposition process and simulated the temperature change of deposition process using numerical simulation. The relationship of depositing time with initial temperature,the number of depositing layer,environment temperature during the ice part building process and waiting time between layer and layer was analyzed and the minimum waiting time was found with a better depositing efficiency. The experiment result is also agree with the model proposed.